2000
DOI: 10.1063/1.481556
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic coupled cluster calculations for neutral and singly charged Au3 clusters

Abstract: Relativistic coupled cluster studies are performed for the structures, dissociation energies, ionization potentials and electron affinities for Au, Au2 and Au3. The calculations show that the upward shifts of the ionization potentials and electron affinities of Aun clusters by approximately 2 eV compared to Cun or Agn base on relativistic effects. Au3+ is predicted to adopt a trigonal planar structure (D3h, A11), Au3 a E⊗ε Jahn–Teller distorted structure (C2v,2A1) 0.1 eV below the linear Σu+2 arrangement, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
84
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 81 publications
18
84
1
Order By: Relevance
“…Once more, the relativistic effects are responsible for the larger values of the gold clusters. It is in accordance with the experimental data displayed in Figure 2 of Wesendrup et al 29 …”
Section: Stabilitysupporting
confidence: 81%
See 3 more Smart Citations
“…Once more, the relativistic effects are responsible for the larger values of the gold clusters. It is in accordance with the experimental data displayed in Figure 2 of Wesendrup et al 29 …”
Section: Stabilitysupporting
confidence: 81%
“…33,34 We would like to cite the experiments about vertical ionization potentials and electron affinities performed by some research groups, 28,[35][36][37][38][39] where the results of all studied gold clusters surpass those of the copper and silver ones (see Figure 2 of Wesendrup et al). 29 As a consequence of this finding, the properties and surfaces of the gold clusters will be differently affected. Thus, a study about the variation of such properties with the cluster size will be interesting.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The distorted Au 3 cluster has C 2v symmetry and two possible electronic states, 2 21 showed that even relativistic CCSD͑T͒ calculations with large basis sets predict the 2 A 1 state to be the ground state with the energy splitting between it and the 2 B 2 state of 4.4 kcal/mol. The same authors showed that relativistic MP2 calculations predict the 2 B 2 state to be 0.9 kcal/mol more stable than 2 A 1 .…”
Section: B Results For Aumentioning
confidence: 99%